The Impact of Financial Leasing on Banking Performance by Measuring the EPS Index / Applied and Analytical Research in Some Iraqi Private Islamic Banks for the Period from 2018_2022 - Mahmoud, Hadeel Shakir; Neama, Nagham Hussein (Journal of Ecohumanism, 2024)
This study aimed to analyze the impact of financial leasing revenues on financial performance in the banking sector, by identifying the nature of financial leasing and its benefits, and to know the extent to which banks benefit from financial leasing and its impact on their banking performance, the study relied on the financial statements of two private Iraqi Islamic banks, which provide financial leasing services, by calculating the total return per share and return per share through financial leasing. The study relied on the main hypothesis that financial leasing positively affects the financial banking performance of Islamic banks that adopted this formula. The study reached the conclusion that there is no impact of financial leasing revenues on the financial performance in the study sample combined, as well as the lack of impact of financial leasing revenues on financial performance in all banks representing the study sample, and the reason for this is due to the instability in the economies of these countries, This fluctuation in the volume of financial leasing activity in Arabic countries reflects many of the problems and challenges facing this activity. One of the most important recommendations reached by the research is the need to provide full support to the banking sector by governments to be able to provide financial leasing services and benefit from them, as well as the need to educate administrators in the banking sector about the importance of financial leasing and the expected benefits of using it.